Recent developments on (−)-colchicine derivatives: Synthesis and structure-activity relationship - Ghawanmeh, Abdullah A.; Al-Bajalan, Hussein M.; Mackeen, Mukram Mohamed; Alali, Feras Q.; K. F., Chong (Elsevier, 2019)
(−)-Colchicine, an anti-microtubulin polymerization agent, is a valuable medication and the drug of choice for gout, Behçet’s disease and familial Mediterranean fever. It has a narrow therapeutic index due to its high toxicity towards normal cells. Nonetheless, numerous (−)-colchicine derivatives have been synthesized and studied for their structure-activity relationship and preferential toxicity. Different functional groups such as amides, thioamides, N-arylurea and 8,12-diene cyclic have been incorporated into (−)-colchicine, resulting in derivatives (with moieties) that include electron-withdrawing and electron-donating groups. This review article focuses on recent developments in the chemical synthesis of (−)-colchicine derivatives, the substituents used, the functional groups linked to the substituents, the moieties and biological studies. Moreover, the current classification of derivatives based on the (−)-colchicine rings, namely ring A, B, and C (−)-colchicine derivatives, is discussed. This work demonstrates and summarizes the significance of (−)-colchicine derivatives in the biological field, and discusses their promising therapeutics for the future.